Production and Characterization of Cellulase Enzyme Produced by Bacillus Isolates from Different Sources (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted to produce and characterize cellulaseenzymes from Bacillus isolates and to determine the optimum conditionsfor cellulase activity. Four Bacillus isolates were used: iso 9+ fromcompost and iso13, iso23 and iso20 from soil. The four isolates (9+, 23,13 and 20) gave average cellulase activities of 2.89, 3.12, 3.48 and 3.53Unit/ml, respectively. The pH optimum for cellulases from the fourisolates was 6, and the temperature optima were 45, 60, 60 and 80°C,respectively. Cellulases from isolates 13 and 23 were more thermostableand retained 40.2% and 21.9% of their initial activities after incubationfor 110 min at 90°C. Cellulase was produced under solid statefermentation conditions in maize cobs, sorghum stover or bagassepretreated with 2% hydrochloric acid from the above four isolates as wellas from two more isolates (iso4- and iso2-) which were isolated from cowdung. Maximum cellulase activity was 3.78 Unit/ml from isolate 4- usingbagasse and maize cobs as substrate. These results demonstrated thatBacillus isolates 13, 23, 20 and 9+ produced active thermostableextracellular cellulase. Bagasse and maize cobs are suitable as substraesfor production of the enzyme cellulase under solid state fermentation.
Keywords: Bacillus; cellulase; pretreated lignocellulosic waste; solid state fermentation